Philips Electronics, Chennai A Report On Employee Retention With Special Reference - Ch. Narahar ,; Koneru, Dr.Kalpana. (The journal of contemporary issues in business and government, 2021)
The exploration named on "A Study on representative maintenance procedures with uncommon reference to PHILIPS ELECTRONICS INDIA LIMITED" Chennai was led. Worker maintenance is the precise exertion to hold the present representatives by giving better approaches and to perceive different desires for the representatives. The test isn't just to draw in the skilled representatives and to hold them. The goal of the examination is to break down the hierarchical components affecting the representative maintenance and to discover singular variables driving workers to go away from the association and to analyse the vital conditions to hold the representatives. The investigation has done through graphic examination technique and the assortment of essential information has done through single group testing strategy under likelihood inspecting technique. The exploration configuration continued in this investigation is distinct examination. Poll is utilized to gather essential information and calculated survey is utilized for auxiliary information assortment through books, sites. The organization can execute better workplace to the representatives; they can give appropriate employment pivot to rouse them. Give adaptable work routine to the representatives.